If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(1 + 3b) + 7(7 + -3b) = 30 (1 * 5 + 3b * 5) + 7(7 + -3b) = 30 (5 + 15b) + 7(7 + -3b) = 30 5 + 15b + (7 * 7 + -3b * 7) = 30 5 + 15b + (49 + -21b) = 30 Reorder the terms: 5 + 49 + 15b + -21b = 30 Combine like terms: 5 + 49 = 54 54 + 15b + -21b = 30 Combine like terms: 15b + -21b = -6b 54 + -6b = 30 Solving 54 + -6b = 30 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-54' to each side of the equation. 54 + -54 + -6b = 30 + -54 Combine like terms: 54 + -54 = 0 0 + -6b = 30 + -54 -6b = 30 + -54 Combine like terms: 30 + -54 = -24 -6b = -24 Divide each side by '-6'. b = 4 Simplifying b = 4
| -5p+-4(-p+4)= | | 8-11=-13 | | -7x-3=-38 | | y*86=259 | | -5y+3z=12 | | -4(8+7h)+2= | | 9x+9=3y+6 | | 9+9x=6+3y | | 3ab-ab= | | 2x-=3 | | 3y+6=9x+9 | | -9(-9+3j)= | | 6x+y+8x+2y=180 | | -2(a+1)-3(1-7a)=-24 | | 6x+y+8x+2y=0 | | 2x+4x+6x-2(x+3)=34 | | 6(2j+1)+7= | | 8+4x=5x+4 | | -1+5(x+2)=12x+3-17x | | X+3x+2x+3(x+1)=30 | | 5-16=8.5 | | 3x-6y+9= | | 3(4+10x)+x= | | 8x+4x=5x+4 | | x^4-4x^3-x^2+16x=0 | | 2x-3(-5x+8)=17x-2+8 | | 5(a+4)-6a+1=12 | | -8(y+2)-16=16 | | -1+5(x+2)=12x+3-1x | | 3y^4-13y^2-10=0 | | 28+2x-1=3x+22 | | 19.5(13.3-4.4x)=7.2(0.8x-116) |